Principais fatores associados às variações nos níveis de fecundidade na África Subsaariana - Elisio Sebastião Mazive (2016)
This study explored the richness of heterogeneity of subnational regions (provinces), with respect to the variations observed in fertility levels, to identify key socio-economic, institutional and behavioral factors associated to fertility and measuring its effect on the fertility level in eighteen Sub-Saharan African countries, using data from Demographic and Health Survey (DHS). This thesis was conducted in order to find answers to the following questions: (i) how the perception of change in the level of fertility between two successive DHSs can be induced by the data quality issue? (ii) what are the main factors associated to fertility level in SSA, considering the last two rounds of DHSs? (iii) what is the effect of the associated factors on the level of fertility? are there differences in the effect of the associated factors among the regions where fertility has fallen and where it did not lowered? Empirical evidence showed that fertility transition in SSA can not be attributed to the quality of data. Changes in socioeconomic, institutional and behavioral factors related to fertility are the most important factors that influence variations in fertility levels observed in this region of Africa. The variables that had a significant effect on the level of fertility in both rounds are: proportion of women living in urban areas, the proportion of women married or in union and median duration of birth intervals. Comparing regions where fertility declined with the regions where did not fall, it is concluded that there are differences between the fertility associated factors in both the next-to-last and the last round of DHSs.